Acquisition of Some Grammatical Categories in Romani (Gypsy) Language by Preschool Rural Roma Children in Bulgaria - Хусейн С. Кючук C. (Христо Кючуков) (Preschool Education: Global Trends, 2025)
The goal. The paper presents research findings from a small study with Roma (Gypsy) children living in a small village in Southeast Bulgaria.